A Colorimetric Method for the Determination of the Exhaustion Level of Granular Activated Carbons Used in Rum Production - Harold Crespo Sariol; Kenny Vanreppelen; Jan Yperman; Ángel Brito Sauvanell; Robert Carleer; José Navarro Campa (Beverages, 2016)
Spectrophotometric measurement applied on saturated granular activated carbon (GAC) is not yet explored. A colorimetric method in the visible range has been developed in order to determine the exhaustion level of GAC used in rum production. Aqueous ammonia solution has been used as an indicative agent to determine the extraction rate of taste compounds within the rum production process and the exhaustion degree of the GAC. The colorimetric results showed excellent correlation with the iodine number and the contact pH. The proposed colorimetric method opens possibilities for rum producers to improve the management and economical use of the activated carbon at the industrial scale.